Habitat Effect on Allometry of a Xeric Shrub (Artemisia ordosica Krasch) in the Mu Us Desert of Northern China - Weiwei She (Forests, 2015)
Allometric models are useful for assessment of aboveground net primary productivity (ANPP) and aboveground biomass (AGB) of forests and shrubs, and are widely implemented in forest inventory and management. Multiple forms of allometric models have been used to estimate vegetation carbon storage for desert shrubland, but their validity for biomass estimation has not been tested at a region scale with different habitats. To verify the validity of habitat-specific models, general models (combining data from all habitats/sites), and previously developed models for biomass prediction, we developed both general models and habitat-specific models for aboveground biomass and ANPP of Artemisia ordosica Krasch, a dominant shrub of the Mu Us Desert. Our results showed that models based on crown area or canopy volume consistently explained large parts of the variations in aboveground biomass and ANPP. Model fitting highlighted that general allometric models were inadequate across different habitats, and habitat-specific models were useful for that specific habitat. Previous models might be inappropriate for other sites because of site quality differences. There was a strong habitat effect on the allometric relationships of A. ordosica. Although our study is a case in point, the results indicate that allometric models for desert shrubs should be used with caution and require robust validation if adopted from other studies or applied to different sites/habitats.